2015
DOI: 10.2196/mhealth.4263
|View full text |Cite
|
Sign up to set email alerts
|

Basal Temperature Measurement Using a Multi-Sensor Armband in Australian Young Women: A Comparative Observational Study

Abstract: BackgroundThe menstrual cycle is a key marker of health in women of reproductive age. Monitoring ovulation is useful in health studies involving young women. The upward shift in basal body temperature, which occurs shortly after ovulation and continues until the next menses, is a potentially useful marker of ovulation, which has been exploited in clinical and research settings.ObjectiveWe investigated the utility of BodyMedia SenseWear (BMSW) in monitoring ovulation in young women by analyzing the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Krauchi et al [4] reported a similar pattern of temperature changes in a menstrual cycle between BBT and skin temperature. In contrast, Wark et al [13] reported poor agreement between BBT and the mean upper arm skin temperature measured at 10-, 30-, 60-, 90-, and 120-minute intervals before waking.…”
Section: Principal Findingsmentioning
confidence: 94%
See 3 more Smart Citations
“…Krauchi et al [4] reported a similar pattern of temperature changes in a menstrual cycle between BBT and skin temperature. In contrast, Wark et al [13] reported poor agreement between BBT and the mean upper arm skin temperature measured at 10-, 30-, 60-, 90-, and 120-minute intervals before waking.…”
Section: Principal Findingsmentioning
confidence: 94%
“…After the initial test, the participant continued doing the LH test daily until a positive result, which was shown as a stable smiling face symbol on the device, or until the next menstruation. A positive result indicates an LH surge, which typically occurs 1 day before ovulation [13]. Participants reported the LH test results in the dedicated field of their Ava app.…”
Section: Lh Testmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted, however, the days when the temperature would have been influenced by other events such as illness, medication, or a sleepless night. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%